2014
DOI: 10.1111/are.12674
|View full text |Cite
|
Sign up to set email alerts
|

A detailed description of pearl-sac development in the black-lip pearl oyster,Pinctada margaritifera(Linnaeus 1758)

Abstract: Appropriate development of the pearl-sac in pearl oysters is an important factor influencing the quality of cultured pearls. In this study, a total of 110 black-lip pearl oysters (Pinctada margaritifera) with a mean (AE SE) antero-posterior measurement of 110.82 AE 0.41 mm and dorsoventral measurement of 112.06 AE 0.45 mm were grafted to allow histological examination and chronological description of pearl-sac development in this species. Beginning 2 days after grafting, oysters were sacrificed regularly until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…While no obvious structural anomalies in the pearl-sac were identified, close proximity of byssus threads to the pearl-sac in some samples indicated that perhaps pressure applied to the pearl-sac by byssus or associated muscles may be involved in circle formation (Kishore and Southgate, 2014). Accepting that the nucleus or developing pearl rotates within the pearl-sac (Cartwright et al, 2013), then pressure applied at a single point on the pearl-sac could result in a concentric anomaly on the pearl.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…While no obvious structural anomalies in the pearl-sac were identified, close proximity of byssus threads to the pearl-sac in some samples indicated that perhaps pressure applied to the pearl-sac by byssus or associated muscles may be involved in circle formation (Kishore and Southgate, 2014). Accepting that the nucleus or developing pearl rotates within the pearl-sac (Cartwright et al, 2013), then pressure applied at a single point on the pearl-sac could result in a concentric anomaly on the pearl.…”
Section: Discussionmentioning
confidence: 95%
“…A second larger nucleus (generally of similar size to the harvested pearl) is then inserted into the pearl-sac through the incision that will subsequently heal. The pearl-sac that develops from the initial graft grows around the nucleus (Kishore and Southgate, 2014) and subsequent and continual deposition of nacre onto the nucleus is likely to result in increasing tension within the pearl-sac. There is no doubt that cutting into the pearl-sac to remove first graft pearls and subsequent insertion of a second nucleus will result in changes in tension within the pearl-sac.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent proliferation of the saibo forms a pearl-sac, which envelopes the nucleus, and epithelial cells within the pearl-sac secrete nacre onto the nucleus to produce a cultured round pearl [2e6]. The process of pearl-sac formation takes less than two weeks in the black-lip pearl oyster, Pinctada margaritifera (Linnaeus, 1758) [6] but around 18e24 months is required to produce pearls with a commercially acceptable nacre thickness [2,7]. Saibo has been shown to have a major influence on the quality of resulting pearls [8e10] with, for example, the colour of a cultured pearl being very similar to that of the nacre of the donor oyster shell [8,9].…”
Section: Introductionmentioning
confidence: 99%